2012
DOI: 10.1096/fj.11-198853
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin couples iron and fatty acid metabolism

Abstract: A physiological relationship between iron, oxidative injury, and fatty acid metabolism exists, but transduction mechanisms are unclear. We propose that the iron storage protein ferritin contains fatty acid binding sites whose occupancy modulates iron uptake and release. Using isothermal microcalorimetry, we found that arachidonic acid binds ferritin specifically and with 60 μM affinity. Arachidonate binding by ferritin enhanced iron mineralization, decreased iron release, and protected the fatty acid from oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Arachidonic acid (ARA) is one of the most abundant fatty acids in the brain and its disturbed metabolism may be associated with neurological disorders such as AD and bipolar disorder [144]. Interestingly, Bu et al [145] recently reported a 60 µM affinity specific binding site of ferritin for ARA. Also, they described that its binding enhances iron mineralization and decreases iron release at the same time that protects the fatty acid from oxidation.…”
Section: Section 5)mentioning
confidence: 99%
“…Arachidonic acid (ARA) is one of the most abundant fatty acids in the brain and its disturbed metabolism may be associated with neurological disorders such as AD and bipolar disorder [144]. Interestingly, Bu et al [145] recently reported a 60 µM affinity specific binding site of ferritin for ARA. Also, they described that its binding enhances iron mineralization and decreases iron release at the same time that protects the fatty acid from oxidation.…”
Section: Section 5)mentioning
confidence: 99%
“…Important electrostatic contacts such as hydrogen bonding, are not represented in this binding site. Given our recent finding that the appoferritin “anesthetic site” is a fatty-acid binding site, 26 the apoferritin qHTS may prove to be a useful screening tool for finding fatty acid receptor or enzyme ligands. Additionally, the lack of GABA A R specificity could be considered an asset in finding anesthetic chemotypes that engage entirely novel anesthetic target, as may have occurred here.…”
Section: Discussionmentioning
confidence: 99%
“…Crystallographic studies of mammalian ferritins revealed that the pockets at the interface between two‐fold axis‐related monomers are available to bind organic molecules, including protoporphyrin, anaesthetics, and fatty acids (FA) . Therefore, it has been suggested that, besides its iron‐storage function, ferritin plays a role in lipid metabolism; a hypothesis that is supported by evidence of functional coupling between iron and fatty acid metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…Crystallographic studies of mammalian ferritins revealed that the pockets at the interface between two‐fold axis‐related monomers are available to bind organic molecules, including protoporphyrin, anaesthetics, and fatty acids (FA) . Therefore, it has been suggested that, besides its iron‐storage function, ferritin plays a role in lipid metabolism; a hypothesis that is supported by evidence of functional coupling between iron and fatty acid metabolism . The crystal structure of the HoSF‐arachidonate complex (PDB 4DE6) reveals that the bound ligand has a U‐shaped conformation (Figure c), characteristic of FA located in the cavity of fatty acid binding proteins, and is close to residues E56, E57 and E60, which form the mineral nucleation site, as recently demonstrated for human homopolymeric l ‐ferritin .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation